STRoke Adverse Outcome is Associated with NoSocomial Infections (STRAWINSKI): Procalcitonin Ultrasensitive-Guided Antibacterial Therapy in Severe Ischaemic Stroke Patients – Rationale and Protocol for a Randomized Controlled Trial. Issue 7 (October 2013) - Ulm, Lena; Ohlraun, Stephanie; Harms, Hendrik; Hoffmann, Sarah; Klehmet, Juliane; Ebmeyer, Stefan; Hartmann, Oliver; Meisel, Christian; Anker, Stefan D.; Meisel, Andreas
Rationale: Stroke-associated pneumonia is one of the most common causes of poor outcome in stroke patients. Clinical signs and laboratory parameters of stroke-associated infections are often inconclusive. Biomarkers may help to identify stroke patients at high risk for pneumonia and to guide physicians in an early antibiotic treatment, thereby improving stroke outcome. Aim: The aim of the present study is to investigate whether procalcitonin ultrasensitive-guided antibiotic treatment improves functional outcome after severe ischaemic stroke by early treatment of pneumonia. Design: STRAWINSKI is an investigator-initiated, multicentre, randomized, controlled trial with blinded assessment of outcome comparing procalcitonin ultrasensitive-guided antibiotic treatment with standard care. Study: 200 patients with ischaemic stroke in the middle cerebral artery territory and a score >9 on the National Institutes of Health Stroke Scale will be included and randomly assigned to two groups. One group will receive procalcitonin-based antibiotic therapy guidance; the other group will receive standard stroke unit care. Outcomes: The primary endpoint is functional outcome at day 90 after stroke on the modified Rankin Scale, dichotomized as favourable (0–4) or unfavourable outcome (5, –6 ). Secondary endpoints are time to first event of death, rehospitalization, or recurrent stroke; death rate, infection rate, and days with fever up to day 7; length of hospital stay and hospital discharge disposition; shift analysis of the modified Rankin Scale; Barthel Index and days alive and out of hospital at day 90; use of antibiotics until day 90; and modified Rankin Scale, Barthel Index, and infarct volume at day 180.